SYNTHESIS AND INFRARED STUDY OF POLYNUCLEAR DABCO ADDUCTS WITH NiCl2 AND CuCl2 - MAMADOU NDIAYE; ABDOULAYE SAMB; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2015)
The proposed structures for the studied adducts - DABCO.3[NiCl2·2H2O].EtOH and 2DABCO.3CuCl2.4EtOH or 3DABCO. 4CuCl2.5EtOH are discrete with two or three metallic components, the environments around the Nickel centres being octahedral or square planar, while being octahedral , linear or a square based prism around the Copper centres, the DABCO behaving as a monodentate or bridging bidentate ligand or being lattice. Extra intermolecular interactions via hydrogen bonds when considered, may lead to supramolecular architectures.